DIVERSIFICATION AND INNOVATION OF TEMPE PROCESSED PRODUCT’S TO IMPROVE COMPETITIVENESS IN SMALL AND MEDIUM-SIZED ENTERPRISES TEMPE BUSINESS IN MEKAR BARU VILLAGE - Ombi Romli; Arta Rusidarma Putra; Oki Nurdiansyah (Yayasan Education and Social Center, 2022)
At the moment, many small and medium-sized business actors are either pursuing or even starting a business within the realm of small and medium-sized cottage industries. The UKM of Tempe Mekar Baru is a forerunner in service-oriented commercial enterprise. It is in the Kabayan Village of the Mekar Baru Village of the Kopo District of the Serang Regency of the Banten Province. This business is owned by Mr. Wasis, who also serves as the president. One of the most significant activities contributing to the economy is the production of tempe. However, there are stumbling blocks in tempeh production that eventually become problems. The main issue for tempe artisans is the fluctuating demand for tempe, which is caused by many factors that cause a lack of buyer interest in tempe itself, which in turn causes some tempe to be damaged and not sold, resulting in a decline in sales. Therefore, it is necessary to innovate the product to transform processed tempe into an innovative product and foster sustainable business development. This Product Knowledge Management (PKM) has been developed to innovate processed tempe products, diversifying tempe products. And it is increasing the production capacity of processed tempe with numerous variants of processed products, including Tempe chips, Tempe egg rolls, Tempe nuggets, and others. This PKM utilizes mentoring activities, increases production capacity, introduces the market share of processed tempeh, and integrates e-commerce marketing into the activity evaluation stage. These are the method or approaches that took. In this PKM program, the anticipated results include an increase in the total number of sales, production, and the development of a method for the Mekar Baru UKM to maintain a sustainable marketing strategy for the tempe that it processes to the next step